Harmonizing Pancasila with Noble Technological Values amidst Digitalization - Daffana, Ananda Rizky (Journal of Digital Law and Policy, 2024)
In the current epoch marked by the swift progression of digitalization, the convergence of enduring principles and state-of-the-art technology assumes a heightened significance. This paper delves into the confluence of Pancasila, the fundamental philosophy of Indonesia, with the dynamic landscape of digitalization. Employing a literature review approach, the research undertakes an exploration of existing scholarly works to shed light on the ways in which Pancasila, anchored in its core tenets of justice, unity, democracy, and humanity, can synchronize with and provide guidance for technological progress. The examination focuses on elucidating how the incorporation of Pancasila can cultivate ethical and conscientious conduct within the digital domain, fostering a societal ethos that champions noble values while embracing the advancements of technology. Through a meticulous analysis of pertinent literature, this article aspires to offer nuanced perspectives on the potential synergy between Pancasila and digitalization. Its ultimate goal is to contribute to the development of a harmonious coexistence between technology and moral values within the Indonesian context. By navigating through the intersections of tradition and innovation, the study seeks to provide valuable insights that pave the way for a balanced integration of Pancasila principles into the rapidly evolving technological landscape, fostering a society where ethical considerations remain at the forefront of progress.